Do Corporate Social Responsibilities Support Its Financial Performance? Evidence of the Listed Firms in Vietnam - Minh, Tran Dang Thanh; Hong, Pham Thi Thu; Anh, Le Thi (Jurnal Ekonomi & Studi Pembangunan, 2022)
In the latest decades, corporate social responsibilities (CSR) are incrementally noticed in emerging countries regarding to the surge of globalization and the advance of social concerns. However, there exist opposing arguments on how CSR practices influence a firm’s financial performance (CFP), either in theoretical or empirical perspectives, causing many managers’ hesitation in CSR engagement. This study, therefore, examines the impacts of CSR on CFP, considering the individual effect of each CSR endeavor by using the data from listed firms’ financial statements during the period 2015-2019 and panel regression analysis methods. The findings reveal inconstant effects of different CSR activities on CFP. Specifically, a firm’s fulfillment of shareholders’ and customers’ interests contributes to raise its profitability, while its engagement in the benefits of employees and creditors causes a reduction in financial returns. Interestingly, the correlations between firms’ responsibilies towards regulators and suppliers and CFP are statistically insignificant. Furthermore, we make pairwise marginal comparisons to identify the distinctions of CSR-CFP relations across industries. The results only indicate that listed firms in Utilities sector have the lower level of CSR intensity than those in Consumer Discretionary and Consumer Staples sectors. The implications and limitations are also discussed in this study.